A study on complications in ultrasound guided catheterization of the internal jugular vein - KS, Henjarappa; Havaldar, Pavan P.; Shaik, Hussain Saheb (International Journal of Research in Medical Sciences, 2017)
Background: With the advanced knowledge in medical monitoring, ever increasing value has been placed on the establishment of central venous catheter. During the past few years, monitoring of central venous pressure has become an important aid in the management of critically ill patients. Doppler ultrasound was first used to assist central venous catheter insertion in 1984. Ultrasound has been applied to describe the anatomy of the IJV and to evaluate various techniques for percutaneous cannulation. Real time sonography improves access to the vein compared with the traditional method. Ultrasound guided cannulation limits complications and also the decreases the cannulation time. For reducing the complication in traditional method we have conducted the study through ultrasound guide and observed the complications in new method. Methods: Thirty critical care patients were selected for IJV cannulation either by ultrasound guided technique. This study conducted in department of anesthesiology and critical care, M. S. Ramaiah medical college, Bangalore. Results: In our study there was 100% success rate for first attempt cannulation in USG technique. The mean access time in USG technique was 152.50 ± 63.90 sec. in USG technique arrhythmias were noted in 1 (3.3%) case during the study. No cases of haematoma, pneumothorax, haemothorax, nerve Injury, carotid artery puncture and catheter malposition were noted during the study in USG technique. Conclusion: Ultrasound guided technique improves the cannulation of the IJV with respect to safety, rapidity and comfort to the patient during the procedure.